Torture Porn in the Wake of 9/11 : Horror, Exploitation, and the Cinema of Sensation - Kerner, Aaron, 1972- (Book collections on Project MUSE., 2015)
Saw, Hostel, The Devil's Rejects: this wave of horror movies has been classed under the disparaging label "torture porn." Since David Edelstein coined the term for a New York magazine article a few years after 9/11, many critics have speculated that these movies simply reflect iconic images, anxieties, and sadistic fantasies that have emerged from the War on Terror. In this timely new study, Aaron Kerner challenges that interpretation, arguing that "torture porn" must be understood in a much broader context, as part of a phenomenon that spans multiple media genres and is rooted in a long tradition of American violence. Torture Porn in the Wake of 9/11 tackles a series of tough philosophical, historical, and aesthetic questions: What does it mean to call a film "sadistic," and how has this term been used to shut down critical debate? In what sense does torture porn respond to current events, and in what ways does it draw from much older tropes? How has torture porn been influenced by earlier horror film cycles, from slasher movies to J-horror? And in what ways has the torture porn aesthetic gone mainstream, popping up in everything from the television thriller Dexter to the reality show Hell's Kitchen? Reflecting a deep knowledge and appreciation for the genre, Torture Porn in the Wake of 9/11 is sure to resonate with horror fans. Yet Kerner's arguments should also strike a chord in anyone with an interest in the history of American violence and its current and future ramifications for the War on Terror.--Provided by publisher